Development and testing of a verified scale for assessment of insufficiency of omega-3 polyunsaturated fatty acids in women of reproductive age - Ivan Yu. Torshin; Natalia I. Tapilskaya; Nana K. Tetruashvili; Olga A. Limanova; Svetlana I. Malyavskaya; Olga A. Gromova (IP Berlin A.V., 2021)
Aim. Sufficient provision of women of reproductive age with omega-3 polyunsaturated fatty acids (PUFA), vitamins and microelements is an important factor in optimizing the course and outcomes of pregnancy. Therefore, in therapeutic practice, methods of non-invasive and rapid assessment of the supply of омега-3-PUFAs in women: docosahexaenoic (DHA), eicosapentaenoic (EPA) acid and synergistic micronutrients are in great demand. Materials and methods. Collection and analysis of data from a cross-sectional study of Russian women of reproductive age (1835 years old, n=1368). Results. A verified 100-point scale for a non-invasive rapid assessment of a woman's status by омега-3-PUFA is proposed. This scale, based on the established correlations between the omega-3 index (% EPA + % DHA in the blood), makes it possible to identify patients with normal values of the omega-3 index in the blood (more than 4%) with a sensitivity of 65% and a selectivity of 88%. Score values less than 60 correspond to an insufficient value of the omega-3 index (sensitivity 81%, selectivity 65%). Conclusion. The correlations established in this study between the reduced supply of omega-3-PUFAs and other micronutrients (vitamins E, K, A, B1, B2, PP, B6, folates, magnesium, selenium, copper and iron) suggest the presence of combined micronutrient deficiencies in women with low value of the score on the developed scale.